Designing and Testing of a Simple Solar Still for Thermal Desalination. - Mujuni, Alex (Kabale University, 2024)
The demand for fresh water production is increasing due to global population growth and industrial expansion. Desalination technology is being increasingly utilized to meet this demand. Solar stills, among various desalination methods, are favored for their low maintenance and affordability, although their output is limited. This study aims to develop and test a straightforward solar still suitable for domestic thermal desalination. Materials such as plastic sheets will be employed to create an efficient water purification system. Additionally, a collection system ensures that condensed water is diverted away from the contaminated source to prevent recontamination. A thermometer will monitor ambient temperature, while rocks or bricks inside the solar still will enhance surface area for better condensation efficiency. The findings demonstrated that using a black basin resulted in 25ml of purified water, whereas a smaller green basin yielded 20ml. This indicates that the black basin's heat absorption accelerated the evaporation rate, thereby increasing water production.